2016
DOI: 10.20517/2394-4722.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Tailored nanocarriers and bioconjugates for combating glioblastoma and other brain tumors

Abstract: Worldwide, the incidence of primary brain tumors is on the rise. Unfortunately, noninvasive drug therapy is hampered by poor access of most drugs to the brain due to the insurmountable blood-brain barrier (BBB). Nanotechnology holds great promise for noninvasive therapy of severe brain diseases. Furthermore, recent bioconjugation strategies have enabled the invasion of the BBB via tailored-designed bioconjugates either with targeting moieties or alterations in the physicochemical and/or the pharmacokinetic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…BBB is compromised in human glioma cells because of the leaky inter endothelial tight junction and poorly differentiated astrocytes that are unable to release essential components for BBB function [31,36]. In this case, it is termed as blood-brain tumour barrier (BBTB) or blood-tumour barrier (BTB) [14] (Figure 1). In low-grade gliomas, the structure and function of the BBTB resemble normal BBB, while in hi-grade glioma, BBB is significantly altered, disrupted.…”
Section: The Blood-brain Barrier (Bbb)mentioning
confidence: 99%
See 1 more Smart Citation
“…BBB is compromised in human glioma cells because of the leaky inter endothelial tight junction and poorly differentiated astrocytes that are unable to release essential components for BBB function [31,36]. In this case, it is termed as blood-brain tumour barrier (BBTB) or blood-tumour barrier (BTB) [14] (Figure 1). In low-grade gliomas, the structure and function of the BBTB resemble normal BBB, while in hi-grade glioma, BBB is significantly altered, disrupted.…”
Section: The Blood-brain Barrier (Bbb)mentioning
confidence: 99%
“…Glial cell originated gliomas include glioblastomas, astrocytomas, schwannomas, oligodendrogliomas, etc. [ 14 ]. According to World Health Organization (WHO), glioma tumours of CNS is classified into four grades based on aggressiveness, Grade I pilocytic astrocytoma, Grade II diffuse astrocytoma, Grade III anaplastic astrocytoma, and Grade IV glioblastoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of small size, easy manipulation of structure and properties, active carrying and controlled release of therapeutic agents, in recent years nanoparticles (NPs) take increased attention from scientists [105, 106]. NPs are 1 to 1000 nm colloidal carriers that can be produced as synthetic or natural.…”
Section: Np‐based Deliverymentioning
confidence: 99%
“…Although, there are no FDA-approved systemic treatments for BCBM to date [41] , patents and studies in the past years have shown promising progress and well-established techniques to overcome the BBB/ BBTB [42] . There are two general strategies adopted to facilitate crossing the BBB; invasive and non-invasive techniques [43] .…”
Section: Targeting Brain Metastasesmentioning
confidence: 99%